Ethnomedicinal plants used for diarrhea by tribals of Meghalaya, Northeast India - Laloo, Damiki; Hemalatha, Siva (Pharmacognosy Reviews, 2011)
Environmental status and diarrhea is regarded as a complex and multidimensional topic. Diarrhea is one of the main waterborne diseases considered to be endemic in many regions of the world and brings the major health threats to the world populations, both in tropical and subtropical poor countries. The state Meghalaya situated in the North-Eastern India is an upland landmass bound by seven districts surrounded within by different tribes. The population is predominantly rural, with 81.41% of the population belongs merely to the scheduled tribes. The state offers a wide range of disease environments, dominated by communicable diseases (35.68%), and diarrhea is one of the water-borne diseases that alter the society of the state. Various factors like poor environmental sanitation, unavailability of safe drinking water, seasonal rainfall, infected foods, infection through fomites, flies, cockroaches, etc. are the main culprit that led to the cause of diarrhea in the state. The local people are very much closely associated with nature, and with their ethnobiological knowledge about the plants available around them, they can easily avert and cure themselves from several disease complications. In this review, the information regarding the traditional method of utilization of 58 plant species that are used to treat and cure diarrhea and dysentery are enlisted briefly.
Keywords: Diarrhea; dysentery; Meghalaya; medicinal plants; sacred groves